2020
DOI: 10.1002/qua.26350
|View full text |Cite
|
Sign up to set email alerts
|

Particle formation and surface processes on atmospheric aerosols: A review of applied quantum chemical calculations

Abstract: Aerosols significantly influence atmospheric processes such as cloud nucleation, heterogeneous chemistry, and heavy-metal transport in the troposphere. The chemical and physical complexity of atmospheric aerosols results in large uncertainties in their climate and health effects. In this article, we review recent advances in scientific understanding of aerosol processes achieved by the application of quantum chemical calculations. In particular, we emphasize recent work in two areas: new particle formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 183 publications
(242 reference statements)
1
41
0
Order By: Relevance
“…The development of GO as implemented in ABCluster, has eliminated this obstacle to a large extent, making a series of productive NPF studies possible [32, 96, 167, 172–197] and revealing valuable insights into atmospheric chemistry (see Figure 7 for some examples). ABCluster has been regarded as a standard tool in this field [198–200]. In a work by Zhang, Francisco, and Zeng [176], the GMs of (H 2 NSO 3 H) x (H 2 SO 4 ) y ((CH 3 ) 2 NH) z (0 ≤ x + y ≤ 3, 0 ≤ z ≤ 2) were searched with ABCluster and were subsequently used in quantum chemical and ACDC simulations.…”
Section: Applicationsmentioning
confidence: 99%
“…The development of GO as implemented in ABCluster, has eliminated this obstacle to a large extent, making a series of productive NPF studies possible [32, 96, 167, 172–197] and revealing valuable insights into atmospheric chemistry (see Figure 7 for some examples). ABCluster has been regarded as a standard tool in this field [198–200]. In a work by Zhang, Francisco, and Zeng [176], the GMs of (H 2 NSO 3 H) x (H 2 SO 4 ) y ((CH 3 ) 2 NH) z (0 ≤ x + y ≤ 3, 0 ≤ z ≤ 2) were searched with ABCluster and were subsequently used in quantum chemical and ACDC simulations.…”
Section: Applicationsmentioning
confidence: 99%
“…10 Among all the available quantum chemistry approaches, density functional theory (DFT) has been the dominant method in the last decade because of its versatility and relatively low computational cost, although higher-level wavefunction-based methods have also been used. 21 Because it has been shown that, in usual atmospheric conditions, only hetero-molecular prenucleation clusters may lead to subsequent new particle formation, 10 computational models of pre-nucleation have focused on the properties of clusters made of different species. 11,12,[21][22][23][24][25][26] However, although a recent compiled database has been published consisting of more than 630 atmospherically relevant clusters containing sulfuric acid, bases, various oxidized organic compounds and water, 25 it does not entirely cover the huge diversity of atmospheric organic compounds and complementary studies are thus needed, in many situations.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the prenucleation clusters that precede the formation of nanoscale atmospheric aerosols are small enough for quantum chemical treatment and are a fundamental component of the atmosphere. [ 22 ] Furthermore, they can be seen as a molecular‐level model of the surface of atmospheric aerosols, to the extent that the solvation shell is sufficiently large.…”
Section: Introductionmentioning
confidence: 99%